2022
DOI: 10.1155/2022/7387581
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among Corneal Biomechanical Parameters, Stiffness, and Thickness Measured Using Corvis ST and Pentacam in Patients with Ocular Hypertension

Abstract: Background. To preliminary explore the correlations among corneal biomechanical parameters, stiffness, and thickness in patients with ocular hypertension (OHT) before and after treatment with topical antiglaucoma medications. Methods. This was a retrospective study that included 35 eyes with newly diagnosed OHT. Axial length (AL), apical corneal thickness, and minimum corneal thickness were measured using Pentacam. The lengths, velocities, and times of the first and second corneal applanations (A1L, A1V, A1T, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A recent study has demonstrated a progressive decrease in the SSI with more advanced keratoconus stages, while the SSI was relatively independent of IOP and corneal central thickness but positively correlated with age [ 37 ]. A recent study showed that in eyes with ocular hypertension, the SSI decreases after initiation of treatment with topical antiglaucoma medications [ 38 ]. Whether this decrease is related to decreased intraocular pressure or drug-related ocular surface damage is still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated a progressive decrease in the SSI with more advanced keratoconus stages, while the SSI was relatively independent of IOP and corneal central thickness but positively correlated with age [ 37 ]. A recent study showed that in eyes with ocular hypertension, the SSI decreases after initiation of treatment with topical antiglaucoma medications [ 38 ]. Whether this decrease is related to decreased intraocular pressure or drug-related ocular surface damage is still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This variation in CCT poses potential inaccuracies when measuring IOP using applanation tonometers during acute ACI episodes [39]. Utilizing noncontact measuring instruments could provide more accurate estimates of IOP in patients active and acute ACI [55]. However, such equipment has not been comprehensively tested in patients with ACI, and their use requires further investigation [56].…”
Section: Plos Onementioning
confidence: 99%